1984
DOI: 10.1161/01.hyp.6.3.391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sodium depletion on inactive and active renin from dog kidney and plasma.

Abstract: SUMMARY The relationship of active renin and inactive renin (trypsin-activated angiotensin-I-forming enzyme) to sodium depletion was examined in renal and peripheral plasma and at the subcellular level in the kidneys of dogs. Subcellular fractionation was carried out by discontinuous sucrose density (1.5 and 1.6 M) centrifugation. Sodium depletion selectively caused a six-to sevenfold increase in the renal content of inactive and active renins in the original homogenate, while the subcellular distribution patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…On the other hand, we found that inactive renin constitutes 20% of total renin activity (active renin + inactive renin) in human renin granules 9 and 0.3% in dog renin granules. 22 We also found inactive renin in microsomal fractions in rat kidney (unpublished observation). Thus, conversion of inactive to active renin during maturation of renin granules appears to be more rapid in dogs and rats than in humans.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…On the other hand, we found that inactive renin constitutes 20% of total renin activity (active renin + inactive renin) in human renin granules 9 and 0.3% in dog renin granules. 22 We also found inactive renin in microsomal fractions in rat kidney (unpublished observation). Thus, conversion of inactive to active renin during maturation of renin granules appears to be more rapid in dogs and rats than in humans.…”
Section: Discussionsupporting
confidence: 52%
“…Trypsin treatment was performed as reported previously. 22 To remove active renin, 5 ml of sample was applied to a pepstatin Sepharose column. The pass-through fraction was concentrated to 5 ml, and the aliquot was incubated with trypsin (100 /Ag/ml) up to 60 minutes.…”
Section: Activation Of Inactive Reninmentioning
confidence: 99%